Fixation of Efficient Method for Separation and Analysis of Alkyl Al koxy Silan Compounds by Gas Chromatography - Dhabab, J.M.; Jalhoom, M.G.; Ibrahim, H.E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Modification of gas chromatographic technique for the separation and determination of methyl ethoy silane compounds which were synthesized by the addition of absolute ethanol to methyl chlorosilane compounds have been elaborated experimentally.  The addition of absolute dry ethanol to methyl chlorosilane compounds in the presence of a dry stream of nitrogen gas led to sweep out the liberated HCl gas. This method was found to be the suitable method for the preparation of methyl ethoxy silane compounds. The optimum parameter selected after careful and precise studies was between 20 â€“ 30 ml \ min to carrieir gas flow rate, while applied temperatures of detector and injection part were 250 Â°C   and 225 Â°C respectively. The results showed that suitable chromatographic column for the separation of methyl chloro silane compounds is 50% [5% dioctyl phthalate ] + 50% [10% OV- 101 ] .While 10 % OV â€“ 101 column was found to be the best for the separation of methyl ethoxysilane compounds . Accordingly  , a linear relationship for the calibration curve between concentration and peak area is achieved for methyl chlorosilane and methyl ethoxysilane . Correlation coefficients here ranged between 1 â€“ 0.9991. The results of percentage RSD alotarned for the methyl chlorosilane and methyl ethoxysilane were 0.512.08 and 0.053-1.37 respectively.